SAT0045 In Early RA, the Multi-Biomarker Disease Activity Score at Different Time-Points is Predictive of Subsequent Radiographic Progression. (10th June 2014) - Hambardzumyan, K.; Bolce, R.; Saevarsdottir, S.; Forslind, K.; Petersson, I.F.; Geborek, P.; Ernestam, S.; Sasso, E.H.; Chernoff, D.; Cruickshank, S.E.; Van Vollenhoven, R.F.
Abstract : Background: The prediction of radiographic progression in early rheumatoid arthritis (eRA) patients is important for optimal treatment. We previously demonstrated that a multi-biomarker disease activity (MBDA) score at baseline (BL) was predictive for radiographic progression over the first year of treatment. Objectives: To evaluate the MBDA score at different time-points and its change during treatment as a predictor of radiographic progression over the first two years of treatment in eRA. Methods: The analyses were performed on radiographic progression of patients from the SWEFOT trial, assessed by van der Heijde modified Sharp scores (SHS) from BL to years 1 and 2 (n=220) and from year 1 to year 2 (n=133); and on the MBDA & disease activity scores (DAS28) and C-reactive protein (CRP) at BL (n=220), month 3 (n=220 & n=205) and year 1 (n=133). Radiographic progression was defined as ΔSHS>5. Mann-Whitney U and Chi-square tests were used for comparisons of disease activity measures between progressors and non-progressors, and for determining significance of proportion of radiographic progressors. Results: The median values of MBDA score, CRP (mg/L) and DAS28 at BL for progressors (n=41) and non-progressors (n=179) were 70 and 58 (p=0.001), 28 and 18 (p=0.049), and 6.1 and 5.7 (p=0.136), respectively. After 3 months of MTX therapy the corresponding values were 48 and 40 (p=0.001), 9 and 9 (p=0.213), and 4.8 and 4.0 (p=0.009), respectively. At each time-point patients with low MBDA score had a lower mean ΔSHS and a smaller proportion of subsequent radiographic progressors than those with low CRP or low DAS28 (table). The highest risk for progression from BL to year 1 or 2 (25% and 42% respectively), or from year 1 to year 2 (36%), was observed among patients with high MBDA score at BL which remained high at 3 or 12 months. In contrast, patients with high MBDA score at BL and low MBDA score at months 3 or 12 had much lower risk for progression (6%, 18% and 4% respectively). All patients with persistent low MBDA score throughout 1 year did not progress radiographically over 2 years. Those who had a moderate MBDA score at BL and achieved low MBDA at months 3 or 12 did not progress either. Conclusions: MBDA scores at BL and at 3 & 12 months of treatment, as well as change in MBDA category were predictive of subsequent radiographic progression during up to 2 years. At all measured time points a low MBDA score or achievement of the latter was associated with low risk for subsequent x-ray progression. Disclosure of Interest: K. Hambardzumyan: None declared, R. Bolce Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, S. Saevarsdottir: None declared, K. Forslind: None declared, I. Petersson Speakers bureau: UCB Pharma, Pfizer, AbbVie, P. Geborek: None declared, S. Ernestam: None declared, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, D. Chernoff Shareholder of: Crescendo Bioscience, Consultant for: Crescendo Bioscience, S. Cruickshank Consultant for: Crescendo Bioscience, R. Van Vollenhoven Grant/research support: Abb Vie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, Crescendo Bioscience, GSK, Janssen, Lilly, Merck, Pfizer, Roche, UCB, Vertex DOI: 10.1136/annrheumdis-2014-eular.3719